Alternative discrete variable protocol for point to point Quantum Key Distribution system - Ahmad Ghazali, Lizal Iswady (2012)
Quantum Key Distribution (QKD) is an enabling technology to current modern cryptography which utilizes nature properties of light to transfer key information safely over an unsecured channel. Via this application, both communicating parties can share an identical secret key for their chosen cryptographic scheme in various applications which demand a protection to their highly important message. A designated key bits reconciliation method is known as QKD protocol. The first ever protocol introduced and popularly used is the Bennett and Brassard 1984 (BB84) protocol. However the implementation with current technology has restricted its primary capability to guarantee the security of secret key establishment. As a result, it is vulnerable to Eavesdropping attack. This leads many works on practical protocol and the most significant contribution having used the same setup as the BB84 protocol is the Scarani, Acin, Ribordy and Gisin 2004 (SARG04) protocol. The SARG04 is more robust against photon number splitting attacks and double the BB84 critical transmission distance. Nevertheless SARG04 protocol still has lower percentage of sifted key bit compared to BB84 protocol. Therefore this study has embarked its objectives on identifying and proposing a new QKD protocol which can improve the robustness while allowing higher final key length. The alternative protocol is designed by combining the existing SARG04 decoding with improved SARG04 decoding (ISARG04). Unlike SARG04 which discards any inconclusive result from his measurement, ISARG04 will always accept the non orthogonal state with half probability of error. The robustness of the proposed protocol is simulated based on simple Intercept Resend attack and photon number splitting attacks in quantum key distribution. This new protocol is robust up to two photons per pulse and has an improvement to secure transmissions of bits at higher link loss, up to 26.7 dB. In summary, this work has presented an improved discrete variable protocol which improved the sifted key length and robust to eavesdropping. It is hope that, this contribution might be a breakthrough for near future QKD protocol.